PISA e o movimento de renovação do ensino de Ciências: indícios de uma aproximação? - Castilho, Danillo Deus (2015)
It is a bibliographical research seeking to reflect about the scientific training offered, presenting an argument that suggests the existence of a link between the International Program on Student Assessment (PISA) and the renewal movement of science education, which was thought by António Cachapuz, Anna Maria Pessoa Carvallho, João Praia and Amparo Vilches. The question we tried to answer was: What is the evidence of the relationship between the guidelines proposed by PISA and the “renewal of science education”? Searching for answers we focus our attention in both, the work entitled “A necessária renovação do ensino das ciências” end the “Informe PISA 2006: competências científicas para el mundo del mañana”. To try to know the characteristics of scientific training that could be prevalent in Science Education, the path we followed was to try to understand both the proposal of renovation and the evaluation given by PISA in 2006. Through the historical and dialectical materialism it was possible to identify, on first place, a distortion on the understanding of Vygotsky's theory, this happened because, of the proposal, this theorist is regarded as socio-constructivist, on second place, the existence of limitations at PISA 2006. In particular, we call attention to the fact that evaluation demands only the understanding of a single epistemological category of sciences from students, named by empiricism. To sum up, we end up suggesting the possibility of the constructivist assumptions work as a link between PISA and the proposed of renewal of science education. Consequently, we conclude that the utilitarian training would still be offered by the Science Education.